1998
DOI: 10.3354/meps167197
|View full text |Cite
|
Sign up to set email alerts
|

Postlarval settling behavior, substrate preference, and time to metamorphosis for red king crab Paralithodes camtschaticus

Abstract: ABSTRACT-Swimming behavior was observed and substrate preference determined for glaucothoe stage postlarvae of the red klng crab Paralithodes camtschaticus In the laboratory. One hundred 1 d old glaucothoe were placed into each of 3 replicate 10 1 aquana, each containing a choice of 3 substrates: sand, gravel, or synthetic fiber mesh. Glaucothoe began settling on the first day, and <10% remained swimming after Day 6. Glaucothoe showed a significant preference for the structurally con~plex mesh substrate. Occup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…In addition, despite the long history of research of this fishing resource (Campodonico et al, 1974;Lovrich, 1997;Stevens, 2014), there have been few works studying the early benthic development phases of this species in southern South America (Lovrich, 1997;Tapella & Lovrich, 2006;Cárdenas et al, 2007;Cañete et al, 2008). Indirect assessments highlight the need to increase our knowledge about factors determining natural mortality and recruitment to improve fishery sustainability (Powell & Nickerson, 1965;Shirley & Shirley, 1989;Stevens & Kittaka, 1998;Shanks & Roegner, 2007;Yáñez et al, 2008;Xue et al, 2008;Smith & Eckert, 2011;Stevens, 2014), as well as to better understand possible ecological bottle necks experienced by populations of large crustacean (Duggins et al, 1990;Cañete et al, 2008;Hall & Thatje, 2009).…”
Section: Implications For Fishery Managementmentioning
confidence: 99%
“…In addition, despite the long history of research of this fishing resource (Campodonico et al, 1974;Lovrich, 1997;Stevens, 2014), there have been few works studying the early benthic development phases of this species in southern South America (Lovrich, 1997;Tapella & Lovrich, 2006;Cárdenas et al, 2007;Cañete et al, 2008). Indirect assessments highlight the need to increase our knowledge about factors determining natural mortality and recruitment to improve fishery sustainability (Powell & Nickerson, 1965;Shirley & Shirley, 1989;Stevens & Kittaka, 1998;Shanks & Roegner, 2007;Yáñez et al, 2008;Xue et al, 2008;Smith & Eckert, 2011;Stevens, 2014), as well as to better understand possible ecological bottle necks experienced by populations of large crustacean (Duggins et al, 1990;Cañete et al, 2008;Hall & Thatje, 2009).…”
Section: Implications For Fishery Managementmentioning
confidence: 99%
“…The association of early juvenile red king crab with complex habitat was first documented in the field (e.g. Powell & Nickerson 1965, Sundberg & Clausen 1977 and only recently demonstrated by laboratory studies to be the result of active habitat selection (Stevens & Kittaka 1998, Stevens 2003, foraging opportunities (Pirtle & Stoner 2010), and predator avoidance (Stevens & Swiney 2005, Stoner 2009). …”
Section: Habitat Structural Complexity and Crab Survivalmentioning
confidence: 99%
“…The early benthic stage is most abundant in complex habitats, including fractured rock, cobbles, and bivalve shells (Sundberg & Clausen 1977, Loher & Armstrong 2000, and complex biogenic habitats formed by macroalgae and structural invertebrates, including hydroids and bryozoans (Sundberg & Clausen 1977, McMurray et al 1984, Rodin 1985. Previous studies of habitat choice by red king crab have demonstrated that settle mentstage red king crab prefer structurally complex habitats over open sand (Stevens & Kittaka 1998) and that juveniles prefer structural invertebrates and macroalgae over sand (Stevens 2003, Pirt le & Stoner 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Resale or republication not permitted without written consent of the publisher gae (Hedvall et al 1998), hydroids (Stevens 2003), gravel (Stevens & Kittaka 1998) and cobble (Linnane et al 2000). High levels of mortality during settlement or soon after are observed widely in marine invertebrates and can substantially alter the distribution of recruits and the structure of the population (Gosselin & Qian 1997, Hunt & Scheibling 1997.…”
Section: Abstract: Substratum · Postlarvae · Settlement Behaviour · mentioning
confidence: 99%